THE STUDENTS' PERCEPTION OF ENGLISH LANGUAGE TEACHING IN THE POST-PANDEMIC ERA - Illananingtyas, Tenika (JURNAL KOULUTUS, 2022)
Educational systems around the world are heavily affected by this outbreak. By Covid 19, online learning became mainstream because there was no traditional classroom instruction. The closest alternative to the offline class. Such a background, student awareness of online learning systems adopted at the university level during the Covid 19 pandemic is in progress. The study aims to identify the student perceptions'. Ease of use and usefulness of online learning based on the Technology Acceptance Model. Analyze factors that influence students' perception of learning English online, especially in the context of EFL. In this study, a descriptive approach based on the survey method and responses from 215 students in Islamic Higher Education of Tribakti were accepted. The data were collected through online surveys and structured interviews. Samples were used to obtain samples, and 215 students were interviewed for further search. Information about their experience during the learning process. Research results show students have a positive attitude toward online learning and therefore accept new things in a learning system. It also empirically demonstrates the importance of online learning during Covid19 at the time of the crisis. Several factors influenced student perceptions. These were perceivers, objects, and situations. Participants agreed to this online learning has emerged as a new way to improve the learning process and can continue to improve the learning performance